Moroccan EFL Students' and Teachers' Readiness for Multicultural Education - Wiame El Houari; Hicham Laabidi (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2025)
This study bridges the gap in the existing literature concerning implementing multicultural education. Examining both students' and teachers' perspectives offers insights into the preparedness of educational stakeholders to embrace multicultural frameworks in EFL settings. The primary aim of this study is to assess the level of readiness for multicultural education among Moroccan EFL students and teachers, and to identify key opportunities and challenges associated with its implementation. A mixed-methods research design was adopted. Quantitative data were collected and analyzed using descriptive statistics through two structured questionnaires administered to 100 EFL students and 70 EFL teachers. Qualitative data was gathered via semi-structured interviews and analyzed thematically to gain deeper insight into teachers' views and experiences in multicultural education. The results were interpreted in a convergent manner to ensure a comprehensive understanding of the research problem. The findings indicated that participants generally had positive perceptions of multicultural education. However, many challenges potentially impede the effective integration of multicultural education within the Moroccan EFL context. Hence, the study presents a set of practical recommendations designed to improve stakeholders' readiness and facilitate their adoption of multicultural practices. This study carries significant implications for students, educators, curriculum developers, and policymakers, as it also opens avenues for future research on multicultural education and its implementation.